Romero: Politics and Utopia - Blanco Torres, Yenifeth Omaira; Iguarán Magdaniel, Maldis Liani; Jaramillo Peñaloza, Yatsira Eliut (Universidad del Zulia, 2020)
Oscar Arnulfo Romero y Galdámez constitutes an important figure in the Latin American religious imaginary. His work transcends the walls of the temples and in a frank preferential option for the poor, he is committed to the building of a new civilization. His political praxis oriented from the lines of the Gospels knew how to recognize injustice in its multiple expressions, denounce military totalitarianisms and in turn infuse a hopeful message in the construction of a more humane society. This essay highlights his political and utopian perspective of his work, the same of a Church that confronts the powerful and makes a common home with the excluded.